PENGARUH PENGENDALIAN INTERNAL, KOMITMEN ORGANISASI DAN MORALITAS INDIVIDU TERHADAP PENCEGAHAN KECURANGAN (FRAUD) PROVIDER JAMINAN KESEHATAN NASIONAL (Studi: Pemberi Pelayanan Kesehatan RSU Mohammad Noer Pamekasan) - jurnalmap map; Febby Mandolang; Chamariyah ÔÇì; Subijanto ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This research was conducted in Fraud Prevention of National Health Insurance Providers with a total sample of 31 people. The objectives of this study are: 1) To find out a description of Internal Control, Organizational Commitment and Individual Morality on fraud prevention, 2) To find out whether Internal Control, organizational commitment and individual morality have a simultaneous effect on fraud prevention, 3). To find out whether Internal Control, organizational commitment, and individual Morality partially influence fraud prevention. The results showed that internal control as a relative strength of the individual in identifying his involvement in the organization. Keyword : Internal Control (X1), Organizational Commitment (X2), Individual Morality (X3) And Fraud Prevention (Y).